Cardiopulmonary exercise testing in aortic stenosis patients before and after aortic valve replacement - Kristofer Hedman; Eva Nylander; Éva Tamás; Carl Bellander; Henric Nilsson (Open Heart)
Background Knowledge about how patients with symptomatic aortic stenosis (AS) perform on cardiopulmonary exercise testing (CPET) is sparse. Since exercise testing in patients with symptomatic AS is not advised, submaximal parameters could be of special interest. We aimed to investigate maximal and submaximal physical capacity by CPET before and 1 year after surgical aortic valve replacement (sAVR) in patients with severe AS.Methods In this prospective longitudinal study, 30 adult patients (age 66±10 years) with severe AS referred for sAVR underwent maximal CPET (respiratory exchange ratio ≥1.05) on a bicycle ergometer before (PRE) and 1 year after (POST) sAVR. Normally distributed data are presented as mean (±SD) and non-normally distributed data are presented as median (IQR).Results Median peak workload increased by 8% from 133 (55) watts at PRE to 144 (67) watts at POST (p<0.001). Median ventilatory threshold (VO2@VT) increased from 1216 (391) to 1328 (309) mL/min (p=0.001, n=28). Mean peak oxygen uptake (peakVO2) was not significantly different between PRE and POST; 1871±441 vs 1937±404 mL/min (p=0.08). The oxygen uptake efficacy slope (OUES) was significantly correlated to PeakVO2 at both PRE (r=0.889, p<0.05) and POST (r=0.888, p<0.05)Conclusion Physical work capacity was improved 1 year following sAVR, in terms of higher median peak workload and VO2@VT. The strong correlation between the submaximal variable OUES and peakVO2 suggests that OUES might be a useful surrogate of peakVO2 in this group of patients where maximal exercise testing is not always recommended.